MATRIX MULTIPLIER BY MODULO FOR CRYPTOGRAPHIC TRANSFORMATIONS - Lutskyi Мaksym; Tynymbayev, Sakhybay; Gnatyuk, Sergiy; Berdibayev, Rat; Polishchuk, Yuliia (Ukrainian Information Security Research Journal, 2023)
The main function of cryptographic methods and means of information protection is to ensure the confidentiality and integrity of data. Data encryption is carried out by specialized means (encryptors), which are based on a certain stable (secure) cryptographic algorithm (symmetric or asymmetric). There are three types of encryptors, that are most widely used for data encryption: hardware, software-hardware and software. Their main difference is not only in the method of encryption and the degree of reliability of data protection, but also it is the price, which often becomes a determining factor for users. Despite the fact that the price of hardware encoders is significantly higher than software, the difference in price is not comparable to a significant improvement in the quality of information protection. Hardware encryption has a number of significant advantages over software encryption, one of which is higher performance. Hardware implementation guarantees the integrity of the encryption process. In this case, the generation and storage of keys, as well as encryption is carried out in the encryption board itself, and not in the computer’s RAM. Given this, the development of high-speed operating units of hardware processors for asymmetric encryption, despite their high cost, is an urgent scientific and applied task. This study considers up-to-date approaches to multiplication of numbers by modulo. The algorithm of multiplication with stepwise formation of partial and intermediate residues is investigated, which in turn does not require preliminary calculations, and all calculations do not go beyond the range of the bit grid of the module. As a result, a synchronous matrix multiplier was developed, which contains n blocks of schemes I, n-1 FPR and a single FIR with an intermediate residue register. These results will be useful for cryptographic transformation in the systems with high speed and security requirements, for example in critical information infrastructure of the state.